2018
DOI: 10.7567/jjap.57.115601
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and rotational domains in orthorhombic ε-Ga2O3 thin films

Abstract: In this study, ε-Ga2O3 thin films were grown by mist chemical vapor deposition on a hexagonal (0001) GaN template and a cubic (111) SrTiO3 (STO) substrate. By analyzing the obtained X-ray diffraction (XRD) φ-scans, it was found that the ε-Ga2O3 epitaxial thin films grown on both GaN and STO exhibited an orthorhombic structure. In addition, a method was proposed to distinguish between hexagonal and orthorhombic structures on the basis of the relationships between the 2θ and χ angles for these structures, obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 41 publications
2
71
1
1
Order By: Relevance
“…Within the c-plane the individual domains are rotated 120 • with respect to each other, forming a pseudo-hexagonal pattern observed in the initial XRD study, whose limited resolution provided a mediated view and did not allow to detect the individual domains. Newer XRD 1,12,24,49,51 and TEM 24,51 analyses confirmed the orthorhombic nature of the κ/ε polymorph. To avoid confusions we will, throughout this work, relate to κ when discussing the orthorhombic polymorph.…”
Section: Crystal Structurementioning
confidence: 76%
See 1 more Smart Citation
“…Within the c-plane the individual domains are rotated 120 • with respect to each other, forming a pseudo-hexagonal pattern observed in the initial XRD study, whose limited resolution provided a mediated view and did not allow to detect the individual domains. Newer XRD 1,12,24,49,51 and TEM 24,51 analyses confirmed the orthorhombic nature of the κ/ε polymorph. To avoid confusions we will, throughout this work, relate to κ when discussing the orthorhombic polymorph.…”
Section: Crystal Structurementioning
confidence: 76%
“…The κ phase was found to thermally transition to β only under annealing at high temperatures T > 700 − 800 • C, 14,35 allowing for applications in devices requiring sufficiently high working temperatures. To date, the orthorhombic phase has been grown successfully 36 on a number of different substrates, including Al 2 O 3 (0001), GaN (0001), AlN (0001), 6H-SiC or β -Ga 2 O 3 (201), using halide vapour phase epitaxy, 14,37,38 atomic layer deposition, 39 metal-organic chemical vapor deposition, 15,18,22,27,30,35,37,[39][40][41][42][43][44] metal-organic vapor phase epitaxy, 1,[45][46][47][48] mist CVD 16,17,32,33,49,50 , plasma-assisted molecular beam epitaxy 51,52 , laser molecular beam epitaxy, 21,53 and pulsed laser deposition 12,13,24,[54][55][56][57] .…”
Section: Introductionmentioning
confidence: 99%
“…It was some years later that Cora et al 27 examined the microstructure of MOVPE-grown e-Ga 2 O 3 on (0001) sapphire by high-resolution TEM: they found that the film was indeed ''pseudo-hexagonal'' as the apparent hexagonal symmetry actually resulted from in-plane 1201 rotational nano-domains of orthorhombic Ga 2 O 3 . They corrected the space group to Pna21 and, in analogy with Al 2 O 3 , suggested this polymorph to be more properly named k. More recently these findings were confirmed by Nishinaka et al 28 In other words, it is possible to obtain phase-pure e-Ga 2 O 3 but one has to be aware that it is not single crystalline; rather it is composed of tiny (201) domains of orthorhombic Ga 2 O 3 separated by 1201 twins, virtually with no dangling bonds. It is the short-range order of the gallium octahedra and tetrahedra included between the oxygen planes that gives rise to such a particular arrangement.…”
Section: Introductionmentioning
confidence: 81%
“…The growth of e-Ga 2 O 3 has been demonstrated on various substrates such as gadolinium gallium garnet (GGG) (cubic), MgO(111), yttria-stabilized ZrO 2 (YSZ)(111), a-(Al x Ga 1Àx ) 2 O 3 (0001), NiO(111), AlN, and GaN. 26,28,85,86 The synthesis conditions that allow for a particular Ga 2 O 3 polymorph strongly depend on the crystallographic mismatch between the substrate and epilayer as well as the surface crystal structure. Some authors have reported that substrates of a cubic material (MgO and YSZ) oriented along the (111) direction allow one to obtain single phase (001)-oriented e-Ga 2 O 3 layers by mist-CVD in a wide range of deposition temperatures (400-700 1C) where typically a-Ga 2 O 3 is obtained on c-plane sapphire.…”
Section: Substrate and Lattice Matchmentioning
confidence: 99%
“…This might be due to the fact that the alloy typically grows relaxed for the thicknesses investigated here, [ 24,26 ] such that only the first few nm should be affected by the lattice mismatch or a thin interfacial layer in a different phase not detectable by XRD compensates the mismatch as was already observed before on other substrates. [ 36,62,63 ] However, the mismatch is still lower than for ITO as alternative back contact layer for κ ‐phase thin films (−15.9% in a ‐ and 12.7% in b ‐direction [ 46 ] ). Further, κ ‐phase layers on ITO typically show an inferior crystalline quality compared with layers grown on c‐sapphire.…”
Section: Resultsmentioning
confidence: 99%